Influencia de factores ambientales y digitales en la aparición de xeroftalmia en estudiantes de la carrera de Contabilidad de la Universidad Técnica de Babahoyo, noviembre 2023-abril 2024. - Vera Rúales, Anthony Leonardo (2024)
The present research project will focus on providing information on the influence of environmental and digital factors in the occurrence of xerophthalmia. Xerophthalmia is a condition characterized by dryness on the ocular surface, it seeks to understand how exposure to environmental settings and prolonged use of digital devices may contribute to its development in the student context. It aims to determine the influence of both environmental and digital factors in the occurrence of xerophthalmia in students of Sixth B of Accounting. The study is quantitative descriptive with a duration of 4 months with a sample of 50 students of the accounting career of the Technical University of Babahoyo, where 4 closed questions were taken based on the objectives where it is evident that 80% believe that exposure to blue light influences the onset of xerophthalmia and 20% do not. On the other hand, in response to the question of whether dry and windy environments cause eye dryness problems, 82% answered yes and 18% no. Regarding the use of protection used in exposure to sunny and dry environments, 56% used it and 44% did not. As for the preventive talks on the subject, 96% approved and 4% rejected. The study showed that prolonged exposure to natural and digital environments has a great impact on ocular health.